2015
DOI: 10.1136/annrheumdis-2015-eular.1945
|View full text |Cite
|
Sign up to set email alerts
|

OP0034 Efficacy and Safety of Mavrilimumab, A Fully Human Gm–CSFR-Alpha Monoclonal Antibody in Patients with Rheumatoid Arthritis: Primary Results from the Earth Explorer 1 Study

Abstract: BackgroundOf patients with RA, ∼40% of do not achieve a minimal acceptable improvement (ACR20) despite modern biologic therapy.1,2,3 Granulocyte-macrophage colony-stimulating factor (GM–CSF) is implicated in RA pathogenesis via myeloid and granulocyte cell lineage activation. In a 12-week Phase IIa study, mavrilimumab, a first-in-class inhibitor of the GM–CSF receptor-α demonstrated a sustained effect via this novel therapeutic pathway in RA.4ObjectivesTo evaluate the efficacy and safety of mavrilimumab in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
3
8
0
Order By: Relevance
“…The analysis showed that patients receiving namilumab (150 and 300 mg) had greater improvements from baseline in DAS28-CRP, TJCs, and SJCs compared with patients who received placebo. These improved efficacy outcomes with namilumab were reported as early as week 2, as has been reported for mavrilimumab [2629]. Considering the size of our study, it was an appropriate approach to analyze the DAS28-CRP profile (AUC) in the 150 and 300 mg namilumab combined group versus placebo.…”
Section: Discussionsupporting
confidence: 70%
“…The analysis showed that patients receiving namilumab (150 and 300 mg) had greater improvements from baseline in DAS28-CRP, TJCs, and SJCs compared with patients who received placebo. These improved efficacy outcomes with namilumab were reported as early as week 2, as has been reported for mavrilimumab [2629]. Considering the size of our study, it was an appropriate approach to analyze the DAS28-CRP profile (AUC) in the 150 and 300 mg namilumab combined group versus placebo.…”
Section: Discussionsupporting
confidence: 70%
“…Although the study was not powered to demonstrate statistical significance between mavrilimumab and golimumab, in sDMARD-IR subgroup, 24-week ACR20, ACR50, and ACR70 response rates seem to be apparently lower in the mavrilimumab-treated patients compared with golimumab (53.8%, 35.9%, and 10.3% vs 69.4%, 44.4%, and 27.8%, respectively) 62. However, the authors argued that the dose adopted in this study might be suboptimal as compared to the one (150 mg eow) predicted as most effective by the previously described exposure–response relationship simulation58 and subsequently confirmed by the results of EARTH EXPLORER 1 study 61. This argument is reasonable because ACR20, ACR50, and ACR70 response rates in the 150 mg group of EARTH EXPLORER 1 study seem to be higher (73.4%, 40.5%, and 13.9%, respectively) compared with the 100 mg group of EARTH EXPLORER 2 study (53.8%, 35.9%, and 10.3%, respectively) and comparable with the golimumab group of EARTH EXPLORER 2 study (69.4%, 44.4%, and 27.8%, respectively).…”
Section: Introductionsupporting
confidence: 68%
“…The most common TEAEs reported were headache, nasopharyngitis, and upper respiratory tract infections 61,62,68. In the first study, two cases of pneumonia were observed (one in the mavrilimumab 30 mg eow group and one in the placebo group),61 whereas in the second study, one pneumocystis pneumonia and one lung disorder were observed in the golimumab group 68. During the open-label long-term extension of both phase IIb studies, the most common TEAEs were bronchitis (4.8%), respiratory tract infection (2%), cholelithiasis (1%), cough (0.8%), and neutropenia (0.8%) 65…”
Section: Introductionmentioning
confidence: 99%
“… 53 54 Moreover, the results of the phase IIb trial met the primary end points (DAS28 and ACR20) with a clear dose–response effect with excellent tolerability. 55 Another compound is MOR103, a fully human mAb directed towards GM-CSF. This alternative approach was tested in a phase Ib/IIa study with promising results, including imaging data.…”
Section: New Biologicalsmentioning
confidence: 99%